(untitled) (Hematology Meeting Reports, 2009)
Venous thromboembolism (VTE) is a common complication in cancer patients. Prevention and treatment of VTE are major issues in cancer patients. For prophylaxis in the surgical setting, once-daily subcutaneous injections of low molecular weight heparin (LMWHs) are as effective and safe as multiple doses of unfractionated heparin (UFH). Extending prophylaxis with LMWH beyond hospital discharge reduces the risk of postoperative thrombosis after abdominal surgery for cancer. The clinical benefit from antithrombotic prophylaxis in medical cancer patients remains uncertain. For the initial treatment of VTE, LMWHs are effective and safe. For the long-term treatment of VTE, LMWHs have been shown to be more effective than the vitamin K antagonists in preventing recurrent VTE in cancer patients. The preliminary observations that LMWHs are associated with reduction in cancer mortality deserve further interest.